2015
DOI: 10.1038/ni.3148
|View full text |Cite|
|
Sign up to set email alerts
|

TET1 is a tumor suppressor of hematopoietic malignancy

Abstract: The TET methylcytosine dioxygenase 1 (TET1) enzyme is an important regulator of 5-hydroxymethylcytosine (5hmC) in embryonic stem cells. Decreased expression of TET proteins and loss of 5hmC in many tumors suggests a critical role for the maintenance of this epigenetic modification. Here we show that deletion of Tet1 promoted the development of B cell lymphoma in mice. Tet1 was required for maintaining normal content of 5hmC, preventing DNA hypermethylation and in the regulation of B cell lineage, chromosome ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
235
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(251 citation statements)
references
References 59 publications
13
235
1
2
Order By: Relevance
“…It was reported that the loss of Tet1 or Tet2 led to hematologic cancers (37,60,61), which are associated with low levels of 5hmC in genomic DNA (62). These results suggest that the defect in vitamin C metabolism might also be involved in cancer development or exacerbate the progression of cancers having Tet mutations.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that the loss of Tet1 or Tet2 led to hematologic cancers (37,60,61), which are associated with low levels of 5hmC in genomic DNA (62). These results suggest that the defect in vitamin C metabolism might also be involved in cancer development or exacerbate the progression of cancers having Tet mutations.…”
Section: Discussionmentioning
confidence: 95%
“…Besides underscoring nonredundant roles for ten-eleven translocation (TET) proteins in normal hematopoiesis and transformation, this reinforces a general function of TET(s) and DNA-methylation control as a tumor suppressor of B-cell malignancies. 13,44 A specific role of Tet3 in the B-cell lineage needs to be identified, however, because Tet3 inactivation does not markedly alter lymphopoiesis in mice (Ko et al 45 and our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, no major member of the DNA methylation control pathway was recurrently found mutated in CLL and malignant B-cell differentiation. [12][13][14][15][16] Another player in B-cell malignant development is the activationinduced cytidine deaminase (AID) gene, which encodes a cytidine deaminase and is known to initiate both class switch recombination and somatic hypermutation, 2 main mechanisms implicated in the maturation of the antibody response. AID expression is tightly regulated, and its aberrant activity has been shown to induce mutations in nonimmunoglobulin genes, thus contributing to cellular transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Tet1-deficient mice on a mixed 129/Sv × C57BL/6 background produce normal-sized litters (10), but display minor behavioral abnormalities and defects in learning, memory, and expression of neuronal activation-related genes (11,12), as well as a tendency to develop B-cell lymphomas relatively late in life (13). Tet2-deficient mice on a pure C57BL/6 background are also viable and fertile; they exhibit mild hematopoietic phenotypes and occasionally develop myeloid malignancies late in life (14,15).…”
mentioning
confidence: 99%